2021
DOI: 10.1029/2021jg006458
|View full text |Cite
|
Sign up to set email alerts
|

Lagged Wetland CH4 Flux Response in a Historically Wet Year

Abstract: By the year 2100, mean global annual CH 4 flux (FCH 4 ) from natural wetlands is projected to increase from 172 Tg CH 4 yr −1 to anywhere between 222 and 338 Tg CH 4 yr −1 depending on the climate scenario (Zhang et al., 2017). Under the best climate scenario of strong climate mitigation (RCP 2.6), wetland methane (CH 4 ) emissions are projected to decline in the 2050s after peaking at ∼225 Tg CH 4 yr −1 . Radiative forcing feedback from wetland CH 4 could account for a large portion of the total radiative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…US‐ALQ is a peat and sedge fen near Allequash Creek (elevation ∼500 m), part of the Flambeau River Basin in the Northern Highlands region and is also a North Temperate Lakes Long Term Ecological Research study site (Benson et al., 2006; Turner et al., 2019, 2021). The wetland is predominantly peat and covers 32 ha of the Trout Lake basin.…”
Section: Methodsmentioning
confidence: 99%
“…US‐ALQ is a peat and sedge fen near Allequash Creek (elevation ∼500 m), part of the Flambeau River Basin in the Northern Highlands region and is also a North Temperate Lakes Long Term Ecological Research study site (Benson et al., 2006; Turner et al., 2019, 2021). The wetland is predominantly peat and covers 32 ha of the Trout Lake basin.…”
Section: Methodsmentioning
confidence: 99%
“…Flux towers are well‐positioned to assess these impacts, as they enable measurement of complementary gases (CH 4 , N 2 O) at a high temporal resolution that enables detection and interpretation of spikes (often called “hot moments”) of gas release associated with sudden changes in water levels or biological conditions (Turner et al, 2021). They must be placed alongside estimates of lateral carbon flows (Arias‐Ortiz et al, 2021; Bogard et al, 2020) and then analyzed in concert with tidal or water flow data.…”
Section: Informing Nbcss With a Full Set Of Tools And Approachesmentioning
confidence: 99%
“…These spatial scaling analyses are complemented by those that focus more on the temporal dimension. Turner et al (2021) noted substantial temporal lags in wetland methane fluxes in response to wetting changes while Yun et al (2022) reported a reversing of carbon dioxide uptake to source observed from decadal flux measurements on the Tibetan Plateau arising from a trend of warming soil temperatures promoting high emissions events outside the growing season. A more novel temporal linkage is noted in Li et al (2022) who found temporal oscillations of atmospheric pressure led to a pumping effect on atmospheric moisture in the vadose zone in soils.…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…Turner et al. (2021) noted substantial temporal lags in wetland methane fluxes in response to wetting changes while Yun et al. (2022) reported a reversing of carbon dioxide uptake to source observed from decadal flux measurements on the Tibetan Plateau arising from a trend of warming soil temperatures promoting high emissions events outside the growing season.…”
Section: A Scale For All Silosmentioning
confidence: 99%